The Application of Teams Games Tournament (TGT) and Teaching Game for Understanding (TGfU) Learning Models on Learning Motivation and Volley Ball Passing Skills - Annisa Alifvia Artha; Abdul Rahman Syam T; Anung Priambodo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aim to examine the application of teams games tournament (TGT) and teaching games for understanding (TGfU) on learning motivation and volley ball passing skills students in grade 8th Muhammadiyah 1 Sidoarjo junior high school. This study uses a qualitative and quantitative approach to experiment research and non randomized control group pretest-posttest design to fix the population and sample. The qualitative approach of this study is filling out  the learning motivation questionnaire, while the quantitative approach is conduct a volley ball passing skills test according to the norm. This approach is carried out befor and after treatment called pretest and posttest. The subjects were 87 students who devided into three groups in VIII-G, VIII-I, and VIII-J class. VIII-G class as a control group were not given a treatment, VIII-I class as the experimental group I (TGT), and VIII-J as the experimental group II (TGfU). Data were analized with descriptive statistics using the SPSS 22.0 program. Based on the data concluded that there was a significant increase in the experimental groups compared to the control group. It’s show that learning motivation in experimental group I (TGT) is increase than experimental group II (TGfU) by 11,18% for TGT and 5,76% for TGfU. Volley ball passing skills test has increase by 19,56% in group I (TGT) and 15,48% in group II (TGfU). The result of this study is TGT and TGfU learning models can improve the level of learning motivation and volley ball passing skill.